Bhabha and his magnificent obsessions - Venkataraman, G. (Ganesan), 1932- (Hyderabad, A.P., India : Universities Press, 1994)
Life and work of Homi Jehangir Bhabha, 1909-1966, Indian physicist.
Includes index.
Keywords: Bhabha, Homi Jehangir, -- 1909-1966.; Physicists -- India -- Biography